PENERAPAN METODE STEPPING STONE DAN VRP (VEHICLE ROUTING PROBLEM) UNTUK TRANSPORTASI PENGIRIMAN HASIL PRODUKSI KELAPA SAWIT - Indah Widya Hanzani; Rima Aprilia; Dedy Juliandri Panjaitan (Smart Education, 2023)
Abstract: Transportation problems are problems that often occur in various countries in the world, especially in Indonesia. Traffic jams, infrastructure deficiencies, and distribution problems can result in substantial losses if not handled properly. PT Inecda is a company operating in the oil palm plantation sector. In the process of distributing production results, of course you need to pay attention because it will greatly influence the overall cost efficiency of the project. Increasing project costs are often caused by suboptimal distribution processes. The method used to solve distribution optimization problems is the Northwest Corner Method (NWC) to determine the initial solution and optimal testing using the Stepping Stone Method. And also the Vehicle Routing Problem (VRP) in the form of a mathematical model for routing problems. From the calculation results, the Stepping Stone method with the Northwest Corner Method (NWC) succeeded in providing optimal results and was able to minimize costs of Rp. 7,127,761.71.Keywords: transportatio; northwest corner method (NWC); stepping stone method;vehicle routing problem; crude palm Oil (CPO) Abstrak: Masalah transportasi adalah permasalahan yang seringkali terjadi di berbagai negara di dunia, khususnya di Indonesia. Kemacetan lalu lintas, kekurangan infrastruktur, dan masalah distribusi yang bisa mengakibatkan kerugian yang cukup besar jika tidak ditangani dengan benar. PT Inecda adalah perusahaan yang bergerak di bidang perkebunan kelapa sawit. Dalam proses pendistribusian hasil produksi, tentunya perlu diperhatikan karena akan sangat berpengaruh terhadap efisiensi biaya proyek secara keseluruhan. Meningkatnya biaya proyek seringkali diakibatkan oleh proses pendistribusian yang tidak optimal. Metode yang digunakan untuk menyelesaikan masalah pengoptimalan distribusi adalah Northwest Corner Method (NWC) untuk menentukan solusi awal dan uji optimal menggunakan metode Stepping Stone Method. Dan juga Vehicle Routing Problem (VRP) dalam bentuk model matematis untuk masalah perutean. Dari hasil perhitungan, metode Stepping Stone dengan Northwest Corner Method (NWC) berhasil memberi hasil optimal dan dapat meminimumkan biaya sebesar Rp. 7.127.761,71.Kata kunci: transportasi; northwest corner method (NWC); stepping stone method; vehicle routing problem; crude palm oil (CPO).